Cellular mechanisms of incretin hormone secretion - Marta Santos-Hernández; Frank Reimann; Fiona M. Gribble (2024)
Enteroendocrine cells located along the gastrointestinal epithelium sense different nutrients/luminal contents that trigger the secretion of a variety of gut hormones with different roles in glucose homeostasis and appetite regulation. The incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are involved in the regulation of insulin secretion, appetite, food intake and body weight after their nutrient-induced secretion from the gut. GLP-1 mimetics have been developed and used in the treatment of type 2 diabetes mellitus and obesity. Modulating the release of endogenous intestinal hormones may be a promising approach for the treatment of obesity and type 2 diabetes without surgery. For that reason, current understanding of the cellular mechanisms underlying intestinal hormone secretion will be the focus of this review. The mechanisms controlling hormone secretion depend on the nature of the stimulus, involving a variety of signalling pathways including ion channels, nutrient transporters and G-protein-coupled receptors.